2022
DOI: 10.1101/2022.05.17.22275235
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Reduced exercise capacity, chronotropic incompetence, and early systemic inflammation in cardiopulmonary phenotype Long COVID

Abstract: BACKGROUNDMechanisms underlying persistent cardiopulmonary symptoms following SARS-CoV-2 infection (post-acute sequelae of COVID-19 “PASC” or “Long COVID”) remain unclear. The purpose of this study was to elucidate the pathophysiology of cardiopulmonary PASC using multimodality cardiovascular imaging including cardiopulmonary exercise testing (CPET), cardiac magnetic resonance imaging (CMR) and ambulatory rhythm monitoring.METHODSIn the Long-Term Impact of Infection with Novel Coronavirus (LIINC) Cohort, we pe… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 131 publications
(373 reference statements)
1
26
0
1
Order By: Relevance
“…We and others have previously reported associations between several of these markers ( e.g . IL-6, TNFα) and LC symptoms (Durstenfeld et al, 2022a, 2022b; Peluso et al, 2021a, 2022a; Phetsouphanh et al, 2022). The lack of association between EBV serology and these markers suggest that there are additional important etiological factors driving PASC and LC symptoms that are not directly related to EBV reactivation.…”
Section: Discussionmentioning
confidence: 99%
“…We and others have previously reported associations between several of these markers ( e.g . IL-6, TNFα) and LC symptoms (Durstenfeld et al, 2022a, 2022b; Peluso et al, 2021a, 2022a; Phetsouphanh et al, 2022). The lack of association between EBV serology and these markers suggest that there are additional important etiological factors driving PASC and LC symptoms that are not directly related to EBV reactivation.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies performed CPET 3-6 months after infection; only one study investigated individuals > 1 year after infection. 25 Nearly half of the studies (16/39, 41%) only included hospitalized individuals (median 73% hospitalized, range 0-100%), and most predominantly included symptomatic individuals (median 89% symptomatic, range 38-100%).…”
Section: Resultsmentioning
confidence: 99%
“…27,58,60 Cardiac limitations were uncommon, but Mancini reported attenuations in preload augmentation 52 and Brown and Szekely reported reduced stroke volume augmentation. 30,33 Five studies reported chronotropic incompetence to be a major cause of reduced exercise capacity, 25,30,44,63,64 and most studies reported a lower peak heart rate among individuals with reduced exercise capacity. One study each specifically reported pulmonary fibrosis, 65 pulmonary vascular limitation, 66 impaired microcirculation, 61 endothelial dysfunction, 67 dysautonomia, 64 and loss of mechanical efficiency 28 as the primary etiology of reduced exercise capacity.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations